Bioengineered 3D electrospun nanofibrous scaffold with human liver cells to study alcoholic liver disease in vitro. Issue 7 (28th June 2021) - Das, Prativa; DiVito, Michael D; Wertheim, Jason A; Tan, Lay Poh
Abstract: Alcohol injury induces hepatic fibrosis which gradually progresses to cirrhosis, sometimes may lead to liver cancer. Animal models are less efficient in mimicking responses of human liver cells, whereas in vitro models discussed so far are majorly based on rodent cells. In this work, a coculture of primary human hepatocytes (PHHs) with LX-2 cells was established on the unmodified (C:F_0:0), collagen-I modified (C:F_1:0), fibronectin modified (C:F_0:1) and 3:1 collagen-I to fibronectin modified (C:F_3:1) 3D electrospun fibrous scaffolds. The effect of alcohol injury was evaluated on this cell-scaffold model at 0–40 μl/ml alcohol concentrations over 14 days of culture period by using the gold standard sandwich culture as the control. Among all the culture groups, C:F_3:1 scaffold was able to maintain translational and transcriptional properties of human liver cells at all concentrations of alcohol treatment. The study reveals that, PHHs on C:F_3:1 were able to maintain ~4-fold and ~1.6-fold higher secretion of albumin than the gold standard sandwich culture on Day 3 and Day 7, respectively. When treated with alcohol, at concentrations of 20 and 40 μl/ml, albumin secretion was also observed to be higher (~2-fold) when compared to the gold standard sandwich culture. Again as expected, in C:F_3:1 culture group on 40 μl/ml alcohol treatment, albumin gene expression decreased by ~2-fold due to alcohol toxicity, whereas CYP2C9, CYP3A4, CYP2E1 and CYP1A2 gene expressions upregulated by ~3.5, ~~4, ~5 and ~15-fold, respectively in response to the alcohol injury. LX-2 cells also acquire more quiescent phenotype on C:F_3:1 scaffolds when compared to the gold standard sandwich culture upon alcohol treatment. Thus, C:F_3:1 scaffold with human liver cells was established as the potential platform to scan alcohol toxicity at varied alcohol concentrations. Thus, it can pave a promising path not only to support functional healthy human liver cells for liver tissue engineering but also to examine potential drugs to study the progression or inhibition of alcoholic liver fibrosis in vitro .